Judicialization of the Right to Health and Institutional Changes in Brazil - Ribeiro, Leandro Molhano; Hartmann, Ivar Alberto (Revista de Investigações Constitucionais, 2016)
The judicialization of the right to health in Brazil may be generating institutional innovations in the system. This judicialization has had unexpected effects, such as disrupting budgetary allocations of public healthcare resources. To deal with such effects, many public authorities directly or indirectly involved with the Brazilian Public Health Care System have created a series of institutional innovations. These innovations aim at i) minimizing the budgetary effects of judicialization and/or ii) decreasing litigation involving the public healthcare system. This chapter highlights two demonstrative cases: the healthcare settlement chambers [Câmaras de Conciliação de Litígios de Saúde] and the centers for technical advisement of judges (Núcleo de AssistênciaTécnica - NAT). This article provides a description of the centers for technical advisement of judges and show the still preliminary attempts to institutionalize extrajudicial forms of settling healthcare litigation.